Calculation of random wave parameters using regression method - Dang Xuan Truong (КНУБА, 2015)
This research introduces a new method to calculate the parameters of random waves. Here we calculate the wave height and period. The process observation data from multiple waves of different conditions is a complex problem for the designers of offshore structures. The regression method is proposed as a new method with high reliability to solve this problem.
Keywords: random waves; regression method; 627.2